2020
DOI: 10.1002/anie.202006075
|View full text |Cite
|
Sign up to set email alerts
|

The Conformational Equilibrium of the Neuropeptide Y2 Receptor in Bilayer Membranes

Abstract: Dynamic structural transitions within the seven‐transmembrane bundle represent the mechanism by which G‐protein‐coupled receptors convert an extracellular chemical signal into an intracellular biological function. Here, the conformational dynamics of the neuropeptide Y receptor type 2 (Y2R) during activation was investigated. The apo, full agonist‐, and arrestin‐bound states of Y2R were prepared by cell‐free expression, functional refolding, and reconstitution into lipid membranes. To study conformational tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 68 publications
1
32
0
Order By: Relevance
“…This suggests that the receptor assumes an overall more rigid conformation in complex with arrestin. Our recent study on the Y2R also confirms that the Y2R in complex with Arr3-3A predominantly assumes a single conformation, concluded from the distinct chemical shifts observed for five out of six Trp residues in the molecule [24].…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…This suggests that the receptor assumes an overall more rigid conformation in complex with arrestin. Our recent study on the Y2R also confirms that the Y2R in complex with Arr3-3A predominantly assumes a single conformation, concluded from the distinct chemical shifts observed for five out of six Trp residues in the molecule [24].…”
Section: Discussionsupporting
confidence: 79%
“…Under the latter conditions, backbone order parameters amounted to surprisingly low values between 0.57 and 0.67 depending on the host membrane, corresponding to remarkable backbone motional amplitudes of the C-H bond vectors of 47 • to 40 • . In a recent study, the site-specific order parameters of all Trp residues, mostly residing in α-helical secondary structures of the Y2R in DMPC membranes, were measured site-specifically using CP excitation with a 700 µs contact time [24]. This study reported Trp order parameters between 0.71 to 0.85 in the apo state.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations